Eye-tracking Research Method in Physics Education Research - Kekule, Martina (Scientia in educatione, 2014)
The paper presents eye-tracking research method and its use in physics education research. The method is widely used in marketing, reading research, in sportsmen education etc., however in PER it is rarely used. The paper presents five studies (and one more from biology education), which concerned students’ problem solving (mechanics and electricity). The method was used for both qualitative and quantitative form of research. The most often used comparison of characteristic connected with eye focus was provided. Students prevalently studying at universities were tested; a number of a sample ranged 11–43. The results show several differences between high and low performing students. Limits of the method are presented as well.